The radioactivity distribution and radiation hazard in honey samples from Italian large retailers. Issue 1 (1st January 2022) - Caridi, F; Venuti, V; Paladini, G; Crupi, V; Belmusto, G; Majolino, D
Abstract: The natural ( 40 K) and anthropogenic ( 137 Cs) radioactivity concentration in twenty-five honey samples of five different typologies ( acacia, chestnut, wildflower, linden and honeydew ), coming from Italian large retailers, was investigated by High Purity Germanium (HPGe) gamma spectrometry. The study was carried out in order to estimate the background levels of detected radionuclides in various honey samples, as well as to assess the dose levels due to their ingestion, taking into account the average yearly direct consumption in Italy and assuming this requirement satisfied from a single kind of honey. Experimental results were compared with the total natural radioactivity value (external + internal) for humans, in order to evaluate any possible radiological health risk.